Maternal influences from birth to yearling in Guzerá cattle. I. Genetic causal components of variance and covariance - Mazza, Maria Cristina Medeiros; Pereira, Carmen Silva; Fonseca, Cleusa Graça (Pesquisa Agropecuaria Brasileira, 2014)
Data from 635 Guzerá calves collected at the Canoas Farm (State of Minas Gerais, Brazil) were analysed. The components of variance and covariance were estimated by intraclass correlation of paternal and maternal half-sibs, offspring-dam and offspring-sire pairs. The variance of maternal effects (σ2Am) were 7.36, 81.34 and 15.76% of total phenotypic variance for birth, weaning and yearling weight, respectively. The estimated negative covariance of additive direct and maternal effects (σ2AoAm) for weaning and yearling weights indicated genetic antagonisms between these effects. The results showed the importance in establishing the adequate age for selection practice in beef cattle.